(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It is need to understand and manage the the Workforce Diversity of Gender professionals The issue women gender diversity is common in most parts of the Hospitality Industry. This regularly comes when women are employee part of today’s workforce.As they are the backbone of country economy. A total 38 men and women food production professional participated in this exploratory research. There are several hypothesis related to age, gender, profession tested with ANNOVA and Z test by using SPPS. Result of the study indicates that gender pay and gender bias is a big issue for many people in the workplace. Regardless of similar issue laws and other laws that have been created to address these issues, Women are still far behind men in pay. Although not all causes of gender pay gaps can be changed, resolutions should be evaluated.